Variations of stable isotope fractionation during bacterial chromium reduction processes and their implications - Zhang, Q; Amor, K; Galer, S; Thompson, I; Porcelli, D (Elsevier, 2018)
Many chemical processes generate subtle but readily measured changes in isotope compositions of elements across the periodic table. The elements involved therefore carry diagnostic information about their chemical histories in complex geochemical or biochemical environments. Distinctive Cr isotope signatures can be used to identify immobilization processes of Cr in the environment, such as microbial Cr(VI) reduction, abiotic Cr(VI) reduction, and adsorption. Here we demonstrate that under well-controlled conditions, Cr isotopes can also be used to distinguish between different biological Cr(VI) reduction pathways. The reduction of Cr(VI) by two facultative anaerobic bacteria, Pseudomonas fluorescens LB 300 and Shewanella oneidensis MR 1, was investigated to determine the conditions under which Cr(VI) is reduced and to quantify the corresponding isotope signatures. The present study considers the effects of a broad range of parameters on Cr isotope fractionation, including bacterial species, electron donors, pH, and respiration pathways (aerobic vs. anaerobic) that must be considered for understanding Cr isotope variations under different experimental and environmental conditions. In the bacterial Cr(VI) reduction experiments, the 53Cr/52Cr isotope ratio of the remaining Cr(VI) increased by up to + 8‰, indicating that lighter isotopes of Cr were preferentially reduced. In aerobic experiments, although Cr reduction rates increased as pH increased from 4 to 8, the fractionation factor did not vary significantly (ε = −3.21 ± 0.18‰). Experiments using different electron donors demonstrated that citrate promoted the greatest Cr reduction rate compared with glucose, acetate, and propionate. Under aerobic conditions, although the Cr(VI) reduction rates varied substantially between different experimental settings, the isotope fractionation factors were indistinguishable between all the environmental conditions examined (ε = −3.1‰), with the exception of when citrate was the electron donor (ε = −4.3‰). Cr reduction rates were generally much faster under anaerobic conditions for both bacteria investigated. The utilisation of different electron donors resulted in the same Cr reduction rates by the bacteria, but fractionated Cr with a broad range of isotope fractionation factors, from − 1.58 ± 0.16‰ to − 4.93 ± 0.36‰. Although it has been proposed in many previous studies that there is an inverse relationship between reduction rates and the fractionation factors, no clear relationship between the reduction rates and fractionation factors was observed in this study. The Cr isotope fractionation factors ε were insensitive to pH and electron donor concentration, but dependent on the type of electron donors and redox conditions in the cultures. This indicates that isotope variations may be used to identify when different biological pathways are involved, and so to investigate metabolic processes. The ε value from all experimental conditions examined ranged between − 1.58 and − 4.93‰, with a mean value at − 3.3‰. While Cr isotopes might be used to separate the effects of abiotic and microbially mediated reduction in environmental sites, the fractionation factors from reduction by individual bacterial species overlap with those from several individual abiotic reduction processes, suggesting that site-specific data (e.g., fractionation factors associated with indigenous bacterial populations and local groundwater chemistry) are required in order to use Cr isotopes to distinguish between different reduction mechanisms.